Channel selection of metagenomic next-generation sequencing in infants pathogen detection: a multicenter cross-sectional study - Yang, Chengcheng; Li, Minxu; Yang, Shumei; Pan, Jianer; Ding, Yue; Yang, Jie (Frontiers in Pediatrics, 2025)
In the neonatal period, infectious diseases associated with high morbidity (e.g., neonatal sepsis and meningitis) are preliminarily assessed using indicators like C-reactive protein (CRP) and procalcitonin, but definitive diagnosis relies on pathogen detection through methods such as blood culture, which is time-consuming and has low sensitivity. To improve diagnostic efficiency, metagenomic next-generation sequencing (mNGS) is increasingly utilized, offering three testing modalities: DNA-only, RNA-only, and combined DNA+RNA channels. This retrospective study analyzed 894 clinical samples (peripheral blood, sputum, bronchoalveolar lavage fluid) to compare detection rates across channels. The overall mNGS positivity rate was 51.9% (464/894), with no significant differences among DNA-only (50.8%), RNA-only (55.7%), and combined channels (49.6%) (p > 0.05). Notably, bronchoalveolar lavage fluid samples exhibited the highest positivity rate (84.57%, 148/175), reaching 97.33% (73/75) with dual-channel testing. Sputum samples showed a 53.7% positivity rate (87/172), increasing to 82.35% (14/17) with dual-channel detection. Conversely, peripheral blood had an overall positivity rate of 43.14% (132/306), with the DNA-only channel outperforming RNA-only and dual channels (45.34% 5s. 43.00% and 34.21%). These findings underscore the importance of channel selection based on sample type to optimize diagnostic accuracy and cost-effectiveness.